INFORMATION SUPPORT FOR BUSINESS GOING CONCERN AUDIT OF AGRIBUSINESS IN MARTIAL ARTS CONDITIONS: THEORETICAL AND PRACTICAL ASPECTS - ALOSHYN, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Business going concern auditing is a critically important tool for ensuring stable and sustainable business operations, especially in conditions of deep crises, such as martial law. For Ukraine’s agricultural sector, which before the full-scale invasion occupied leading positions in global exports (about 40% of all national exports in 2021), the war became a serious challenge. Many enterprises suffered damage to equipment and infrastructure, and lost access to agricultural land. At the same time, farmers demonstrated resilience, partially restored production, and maintained access to international markets. In these conditions, the business going concern audit must be adapted to the realities of martial law. It is important that it includes not only classic financial indicators, but also an assessment of specific risks, such as disruption of logistical chains, physical destruction of property, lack of resources. The key condition for an effective audit is the availability of high-quality information support. Audit information support is a set of systems, data, tools and sources that allow for a timely, complete and reliable assessment of the state of the enterprise and external threats. In the context of martial law, it encompasses: operational analytical information on the availability of logistics routes, price fluctuations, and sales markets; satellite data for monitoring crop conditions; databases on losses, destroyed assets, and insurance coverage levels; governmental and sectoral reporting, including data from the State Statistics Service, the Ministry of Agrarian Policy, and customs authorities; as well as the enterprise’s internal control systems, which must be adapted to crisis conditions. Thanks to effective information support, auditors can timely identify critical points, assess risks, model scenarios for the development of the situation, and form informed conclusions about the ability of the enterprise to maintain its activities. This, in turn, allows agribusiness to make flexible management decisions, reduce the impact of negative factors, and plan strategies to overcome the crisis.